Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cryst11060643
|View full text |Cite
|
Sign up to set email alerts
|

A Phononic Crystal with Differently Configured Double Defects for Broadband Elastic Wave Energy Localization and Harvesting

Abstract: Several previous studies have been dedicated to incorporating double defect modes of a phononic crystal (PnC) into piezoelectric energy harvesting (PEH) systems to broaden the bandwidth. However, these prior studies are limited to examining an identical configuration of the double defects. Therefore, this paper aims to propose a new design concept for PnCs that examines differently configured double defects for broadband elastic wave energy localization and harvesting. For example, a square-pillar-type unit ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…For ambient vibrational energies in low-frequency ranges [20,21], defective local-resonance type PnCs (often referred to as metamaterials) seem to be more suitable relative to Bragg type [22]. Single defects have a narrow operating bandwidth, while multiple defects (e.g., decoupled double defects [23,24], coupled double defects [25] and L-shape defects [26]) can broaden the energy harvesting bandwidth. Multiplefield techniques (e.g., thermal tuning [27,28], electrical tuning [29] and magnetic tuning [30]) allow efficient dynamic adjustment of the energy harvesting operating frequency for adaptation to random environmental frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…For ambient vibrational energies in low-frequency ranges [20,21], defective local-resonance type PnCs (often referred to as metamaterials) seem to be more suitable relative to Bragg type [22]. Single defects have a narrow operating bandwidth, while multiple defects (e.g., decoupled double defects [23,24], coupled double defects [25] and L-shape defects [26]) can broaden the energy harvesting bandwidth. Multiplefield techniques (e.g., thermal tuning [27,28], electrical tuning [29] and magnetic tuning [30]) allow efficient dynamic adjustment of the energy harvesting operating frequency for adaptation to random environmental frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…The weakened interaction between the double defects makes them appear independent. One peak frequency corresponding to each defect is independently manipulated at this point by varying the geometric dimensions of piezoelectric devices attached to each defect [ 42 ] or unit cells surrounding each defect [ 43 ]. Therefore, closely placing the defect band of each isolated defect successfully doubles the bandwidth of a PEH system as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al 30) showed that a magnetoelastic PnC with a point defect could tune its resonance frequency to achieve variablefrequency energy harvesting. Jo et al [31][32][33][34] investigated the influence of the circuit connection between two defects, the supercell size and defect location, and dual-defect decoupling on energy localization. Lee et al 35) investigated the high output performance of a PnC-assisted PEH device by tuning the geometric parameters of the device.…”
Section: Introductionmentioning
confidence: 99%